Menthol Mouth Rinsing Is More Than Just a Mouth Wash—Swilling of Menthol to Improve Physiological Performance - Gavel, Erica H.; Hawke, Kierstyn V.; Bentley, David J.; Logan-Sprenger, Heather M. (Frontiers in Nutrition, 2021)
Interventions which solely act on the central nervous system are gaining considerable interest, particularly products consumed through the oral cavity. The oral-pharyngeal cavity contains a wide array of receptors which respond to sweet, bitter, and cold tastants, all of which have been shown to improve physiological performance. As of late, the ergogenic benefits of carbohydrate, and caffeine mouth rinsing have been widely studied; however, less is known about menthol. It is increasingly recognized that the physiological state and environmental conditions impact the response each product has. While the effects of carbohydrate and caffeine mouth rinsing have been thoroughly studied in both hot and thermoneutral conditions, less is known about menthol as it has only been studied in hot environments. As such, this review summarizes the current knowledge regarding menthol mouth rinsing and exercise modality, frequency of the mouth rinse, mouth rinse duration, and compares two different type of study designs—time trials vs time to exhaustion.